PENGARUH REWARD DAN ICE BREAKER TERHADAP MINAT BELAJAR TEMATIK SISWA DI KELAS VI SEKOLAH DASAR KHATOLIK SANTO YOSEPH 2 NAIKOTEN - Delila Malafu; Roswita Lioba Nahak; Yulsy Marselina Nitte (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2023)
Abstract. The purpose of this research are (1). Knowing the effect of rewards on students' thematic learning interest. (2). Knowing the effect of ice beaker on students' thematic learning interest. (3). Knowing the effect of reward and ice breaker on students' thematic learning interest. In the learning process the teacher must be able to create active and enjoyable learning in accordance with the characteristics of students in order to achieve educational goals. The research method used in this study is a survey method. The population in this study were students of class VI SDK ST.Yoseph 2 Naikoten Kota Kupang, while the samples were all students of class VI, totaling 38 students. Data collection techniques used are questionnaires and documentation. The data analysis techniques in this study were the normality test, homogeneity test, linearity test, multicollinearity test and heteroscedasticity test. The results of data analysis showed a significant value of 0.05% was obtained: (1). Reward has a significant effect on students' thematic learning interest. This is based on the results of the t test known that t count > t table 6.240 > 2.059 and a significant value of 0.05, namely with a contribution of 18.7% to students' thematic learning interest. (2). Ice breaker has a significant effect on students' thematic learning interest. This is based on the results of the t test known that t count >t table is 26,039 >1.628 and a significant value of 0.00 >0.05, namely with a contribution of 23.6% to students' interest in thematic learning. (3). Rewards and ice breakers affect students' thematic learning interest. Based on the F test, it is known that t count >t table is 42.378 > 2.63 and a significance value of 0.000 <0.05 and contributes 31.9% to students' thematic learning interest while the rest is influenced by other variables. This can be interpreted that the independent variables (reward and ice breaker variables) contribute or influence 74.2% of students' thematic learning interest. The remaining 25.8% of students' thematic learning interest is influenced by other variations outside of this study. Abstrak. Tujuan dari penelitian ini adalah (1). Mengetahui pengaruh reward terhadap minat belajar tematik siswa . (2). Mengetahui pengaruh ice beaker terhadap minat belajar tematik siswa. (3). Mengetahui pengaruh reward dan ice breaker terhadap minat belajar tematik siswa. Dalam proses pembelajaran guru harus mampu menciptakan pembelajaran yang aktif dan menyenangkan sesuai dengan karakteristik siswa demi mencapai tujuan pendidikan. Metode penelitian yang digunakan dalam penelitian ini adalah metode survei. Populasi dalam penelitian ini adalah siswa kelas VI SDK ST.Yoseph 2 Naikoten Kota Kupang, sedangkan yang menjadi sampel adalah semua siswa kelas VI yang berjumlah 38 siswa . Teknik pengumpulan data yang digunakan adalah angket dan dokumentasi. Teknik analisis data dalampenelitian ini adalah uji normalitas, uji homogenitas, uji linearitas, uji multi kolinearitas dan uji heterokeditas. Hasil analisis data menunjukan nilai signifikan 0,05% dipereoleh : (1). Reward berpengaruh signifikan terhadap minat belajar tematik siswa. Hal ini berdasarkan hasil uji t diketahui bahwa thitung > ttabel 6,240 > 2,059 dan nilai signifikan 0,05 yaitu dengan kontribsui sebesar 18,7 % terhadap minat belajar tematik siswa. (2). Ice breaker berpengaruh signifikan terhadap minat belajar tematik siswa. Hal ini berdasarkan hasil uji t diketahui bahwa thitung >t tabel yaitu 26.039 > 1,628 dan nilai signifikan 0,00 > 0,05 yaitu dengan kontribusi sebesar 23,6% terhadap minat belajar tematik siswa. (3). Reward dan ice breaker berpengaruh terhadap minat belajar tematik siswa. Hal ini berdasarkan uji F diketahui bahwa thitung > t tabel yaitu 42,378 > 2,63 dan nilai signifikansinya 0,000 < 0,05 dan memberikan kontribusi sebesar 31,9% terhadap minat belajar tematik siswa sedangkan sisanya dipengaruhi oleh variabel lain. Hal ini dapat diinterpretasikan bahwa variabel bebas (variabel reward dan ice breaker) memberikan kontribusi atau pengaruh sebesar 74,2% terhadap minat belajar tematik siswa Selebihnya yakni sebesar 25,8% dari minat belajar tematik siswa dipengaruhi oleh variasi lain di luar penelitian ini.